Report on the Munich Film Festival 2004 - Fisher, Jaimey (New Cinemas: Journal of Contemporary Film, 2004)
Although the Munich festival has long had to play second fiddle to Berlin's A-list event, it remains in many ways more important for Germany's media industry. This status is reflected in the character and constitution of both film festivals: while Berlin offers a higher profile venue for international competition and independent film - it usually attracts more Hollywood stars as well as film buyers - the Munich festival's biggest prizes are intended for domestic talent. This year's festival was one of the best of the last several, not only because it offered excellent individual films, but also because of its productive mixture of experienced directors and relative newcomers.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9uY2luLjIuMy4xOTkvNw